Atlantic Wharf: Redevelopment Of A Historic Site On Boston's Waterfront - Lee S. Vanzler (Deep Foundations Institute, 2011)
Atlantic Wharf involved the construction of a six-level underground parking garage and a 32-story high rise tower along the historic Boston Harbor waterfront. The site, historically known as ?Russia Wharf,? consisted of filled land initially created in the late 1800s by extending the shoreline toward the harbor as the urban population and land needs grew to support expansion of commerce and trade. Redevelopment required solutions to address relics of waterfront structures (granite block seawalls, piles, and piers), weak subsurface soil conditions, tidal groundwater levels, and contaminated soils resulting from previous site usage and filling. The foundation system, consisting of drilled shafts with column loads up to 14,000 kips (62,272 kN), concrete diaphragm wall (slurry wall), and up-down construction methodology, was chosen to address these factors. As a prerequisite for development, selected portions of the façades of the former historic buildings were required to be preserved, protected, and incorporated into the final building configuration. The historic façades were temporarily braced and supported prior to the demolition of the buildings and commencement of below-grade construction. This paper will describe the considerations in the selection of up-down construction methodology along with a discussion of the design and performance of the concrete diaphragm wall and drilled shaft foundations. Up-down construction methodology shortened the overall construction schedule while addressing the lateral bracing requirements for the concrete diaphragm wall and restrictive ground movement tolerances to protect adjacent structures. Below-grade construction was completed in March 2010, and the building was opened for tenant occupancy in January 2011.